FinTech: A New Hedge for a Financial Re-intermediation. Strategy and Risk Perspectives - Omarini, Anna (Frontiers in Artificial Intelligence, 2020)
The emergence of new technologies and players, along with a favourable regulatory framework (PSD2 Directive) are changing the banking industry. FinTechs and TechFins have allowed the introduction of new services, and changed the way customers interact to satisfy their financial needs. The FinTech landscape is ever evolving in the market. Different business value propositions are entering the financial services industry moving from increasing the user’s experience to developing a time to market framework for banks to innovate products, processes and channels, increase the cost efficiency and looking for a “partnering on order” to light the regulatory burdens for banks. The many businesses of banks are changing their value chains and banks’ business models should do the same accordingly. Strategists could no longer take their value chains as a given; choices have to be made on what needs to be protected and maintained, what abandoned and the new on coming to make banks evolving and become more resilient in doing their job. Banking is shifting significantly from a pipeline, vertical paradigm, to open banking business models where open innovation, modularity and ecosystem-based bank’s business model may become the ongoing mainstream and paradigm to work for it. Opportunities and threats for banks are many and new ones to re-gaining their role in the market throughout a re-intermediation process.